Assessment of Atmospheric Oxidizing Capacity Over the Beijing‐Tianjin‐Hebei (BTH) Area, China. Issue 7 (1st April 2021) - Feng, Tian; Zhao, Shuyu; Hu, Bo; Bei, Naifang; Zhang, Xiu; Wu, Jiarui; Li, Xia; Liu, Lang; Wang, Ruonan; Tie, Xuexi; Li, Guohui
Abstract: The atmospheric oxidizing capacity (AOC) plays a key role in atmospheric chemistry, determining the removal of most reduced gases in the atmosphere. In this study, we assess the summertime AOC from 7 to 22 June 2014 associated with a field campaign conducted at Wangdu in the Beijing‐Tianjin‐Hebei region (BTH), China using the WRF‐Chem model. The model reasonably well reproduces the incident solar radiation, ambient O3 and fine particulate matter (PM2.5 ) concentrations, the photolysis rates of O3 and NO2, and radical concentrations against measurements in the BTH. The model results show high daytime AOC levels in urban areas and relatively low AOC in remote areas of the BTH. The diurnal cycle of the AOC exhibits a unimodal pattern with peaks at noon. OH radical contributes about 68% of the daily average AOC in Beijing, followed by O3 (27%) and NO3 (5%). At Wangdu, the production rate of OH radical reaches around 13 ppb h −1 at noon, which is mainly resulted from the reaction of HO2 with NO. The OH radical loss is primarily contributed by reactions with volatile organic compounds, followed by CO and NO2 . Statistically, the population hourly or afternoon average O3 and Ox (=O3  + NO2 ) concentrations are significantly correlated with the AOC in Beijing, constituting potential simplified tracers to indicate the AOC level. Key Points: The summertime atmospheric oxidizing capacity (AOC) over the Beijing‐Tianjin‐Hebei area is assessed combining a field campaign and WRF‐Chem simulation OH radical contributes about 68% of the daily average AOC in Beijing, followed by O3 (27%) and NO3 (5%) Population hourly or afternoon average O3 and Ox (=O3  + NO2 ) concentrations constitute potential simplified tracers for the AOC level